A 96-wells fluidic system for high-throughput screenings under laminar high wall shear stress conditions - Fonseca, Catarina Gonçalves (2023)
The ability of endothelial cells to respond to blood flow is fundamental for the correct formation and maintenance of a functional and hierarchically organized vascular network. Defective flow responses, in particular related to high flow conditions, have been associated with atherosclerosis, stroke, arteriovenous malformations, and neurodegenerative diseases. Yet, the molecular mechanisms involved in high flow response are still poorly understood. Here, we described the development and validation of a 96-wells fluidic system, with interchangeable cell culture and fluidics, to perform high-throughput screenings under laminar high-flow conditions. We demonstrated that endothelial cells in our newly developed 96-wells fluidic system respond to fluid flow-induced shear stress by aligning along the flow direction and increasing the levels of KLF2 and KLF4. We further demonstrate that our 96-wells fluidic system allows for efficient gene knock-down compatible with automated liquid handling for high-throughput screening platforms. Overall, we propose that this modular 96-well fluidic system is an excellent platform to perform genome-wide and/or drug screenings to identify the molecular mechanisms involved in the responses of endothelial cells to high wall shear stress. [Figure not available: see fulltext.].